Ambulatories and Chapels in the Churches of Macedonia in the 8th–14th Centuries - Freze, Anna A. (Actual Problems of Theory and History of Art, 2023)
Ambulatories and Chapels in the Churches of Macedonia in the 8th–14th сenturies display the variety and contextuality of the chosen design elements. As a whole, the phenomenon stays within the framework of the common Byzantine trends in handling of the periphery bays, using a wide range of options in introducing chapels and ambulatories in the architecture of a church complex. A special group consists of the late Byzantine monuments of Thessaloniki, where the annexes are arranged to envelope the core and end with a pair of eastern chapels. This article suggests to look for the origins of such layout in the middle Byzantine architecture of Constantinople. The extant Macedonian monuments show a special freedom of their master-builders in creating new designs, also by including chapels and ambulatories, leading to the development of new layouts, trespassing the definitions of the settled “canonical” Byzantine architectural types.This research was funded by the Russian Scientific Fund, project No. 20-18-00294-П “Artistic Traditions and Ecclesiastic-Political Ideology in the Medieval Architecture and Art of the Balkans. Macedonian question”.
Keywords: Macedonia; Byzantine architecture; ambulatories; chapels; church architecture